Doxorubicin conjugated with a trastuzumab epitope and an MMP-2 sensitive peptide linker for the treatment of HER2-positive breast cancer - You, Yiwen (Drug Deliv, 2018)
HER2-positive breast cancer correlates with more aggressive tumor growth, a poorer prognosis and reduced overall survival. Currently, trastuzumab (Herceptin), which is an anti-HER2 antibody, is one of the key drugs. There is evidence indicating that conjugation of trastuzumab with chemotherapy drugs, such as doxorubicin (DOX), for multiple targets could be more effective. However, incomplete penetration into tumors has been noted for those conjugates. Compared to an antibody, peptides may represent an attractive alternative. For HER2, a similar potency has been observed for a 12-amino-acid anti-HER2 peptide mimetic YCDGFYACYMDV-NH(2) (AHNP, disulfide-bridged) and full-length trastuzumab. Thus, a peptide, GPLGLAGDDYCDGFYACYMDV-NH(2), which consists of AHNP and an MMP-2 cleavable linker GPLGLAGDD, was first designed, followed by conjugation with DOX via a glycine residue at the N-terminus to form a novel DOX-peptide conjugate MAHNP-DOX. Using HER2-positive human breast cancer cells BT474 and SKBR3 as in vitro model systems and nude mice with BT474 xenografts as an in vivo model, this conjugate was comprehensively characterized, and its efficacy was evaluated and compared with that of free DOX. As a result, MAHNP-DOX demonstrated a much lower in vitro IC(50), and its in vivo extent of inhibition in mice was more evident. During this process, enzymatic cleavage of MAHNP-DOX is critical for its activation and cellular uptake. In addition, a synergistic response was observed after the combination of DOX and AHNP. This effect was probably due to the involvement of AHNP in the PI3K–AKT signaling pathway, which can be largely activated by DOX and leads to anti-apoptotic signals.